Paramacular Acute Middle Maculopathy Associated with Glyceryl Trinitrate - Tryfon Rotsos; Ioannis Giachos; Konstantinos Tyrlis; Chrysanthos Symeonidis; Ekaterini Mani; Ilias Georgalas (Case Reports in Ophthalmological Medicine)
An unusual case of nitroglycerin-induced Paracentral Acute Middle Maculopathy (PAMM) is presented. A 50-year-old patient with sudden vision loss and scotoma was followed up with swept-source optical coherence tomography (SS-OCT), optical coherence tomography-angiography (OCT-A), and fluorescein angiography (FA). An anal fissure treated with glyceryl trinitrate (GTN) 0.2% ointment with headache and dizziness after application was reported. Fundoscopy OS revealed mild retinal venous dilatation and tortuosity with scattered blot hemorrhages and subtle, parafoveal, whitish lesions in the outer retina. SS-OCT revealed diffuse, hyperreflective lesions in the inner plexiform (IPL), inner nuclear (INL), and outer plexiform layers (OPL). OCT-A revealed focal dropout in the deep capillary plexus. FA showed masking due to blot hemorrhages and early punctuate leakage in the inner retina. This entity was identified as nitroglycerin-induced PAMM. Over the following 8 months, after discontinuation of the ointment application, the patient was symptom-free with stable visual acuity. OCT revealed INL/OPL thinning and confirmed complete lesion resolution. This first report of retinal vascular abnormalities due to nitrite ointment provides an insight into an unknown side effect of nitroglycerin ointment use. A dose-dependent correlation between GTN application and retinal vascular abnormalities remains to be confirmed.